Surgical stabilization of concomitant canine medial patellar luxation and cranial cruciate ligament disease - Fauron, Albane H.; Bruce, Mieghan; James, Daniel R.; Owen, Mark A.; Perry, Karen L. (Veterinary and Comparative Orthopaedics and Traumatology, 2017)
Objectives: To compare complication rates and outcomes between cases of concomitant cranial cruciate ligament (CrCL) disease and medial patellar luxation (MPL) treated using extracapsular stabilization and tibial tuberosity transposition (ECS+TTT) and tibial tuberosity transposition and advancement (TTTA).Methods: In a multicentre retrospective study, records from four referral hospitals were reviewed for dogs with concomitant CrCL pathology and MPL treated using ECS+TTT or TTTA. Data retrieved included signalment, partial/complete CrCL tear, MPL grade, treatment performed, occurrence of postoperative complications, and postoperative outcome grade. Associations between surgical procedure and risk of complication and surgical procedure and outcome were investigated using univariable logistic regression and proportional odds logistic regression respectively. Multiple logistic regression was used to explore confounding factors.Results: A total of 72 stifles were evaluated in 66 dogs; 32 stifles were stabilized using ECS+TTT and 40 using TTTA. Overall complications were 2.7 times more frequent in the ECS+TTT group and major complications occurred only in this group. The TTTA group was less likely to suffer complications (17.5%) compared to the ECS+TTT group (46.9%) (p = 0.009) and TTTA cases had lower odds of a poorer clinical outcome (p = 0.047).Clinical significance: Stifles stabilized using ECS+TTT are more likely to suffer from postoperative complications and a poorer clinical outcome when compared to TTTA.Supplementary Material to this article is available online at https://doi.org/10.3415/VCOT-16-10-0148
Keywords: Medial patellar luxation; cranial cruciate ligament disease; tibial tuberosity transposition; extracapsular stabilization; tibial tuberosity transposition and advancement